Індукування саліциловою кислотою тепло- і солестійкості проростків Triticum aestivum L. у зв'язку зі змінами прооксидантно-антиоксидантної рівноваги - Колупаєв, Ю.Є.; Карпець, Ю.В. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2006)
Изучали влияние салициловой кислоты (СК) на тепло- и солеустойчивость проростков озимой пшеницы Triticum aestivum L. Обработка этиолированных проростков повышала их выживание после повреждающего нагрева и солевого (NaCl) стресса. Действие СК вызывало обратимое снижение активности каталазы, повышение активности пероксидазы и накопление пероксидов в корнях и побегах. После нагрева и солевого стресса содержание пероксидов в побегах и корнях проростков, обработанных СК, было ниже, а активность каталазы выше, чем в контроле. Активность пероксидазы после теплового и солевого стрессов в корнях проростков, обработанных СК, была более высокой, чем в контроле, в то время как в побегах таких различий не наблюдалось. Предполагается, что "окислительный всплеск", вызываемый СК, активирует в проростках защитные механизмы, обеспечивающие адекватную реакцию на последующие тепловой и солевой стрессы. The influence of salicylic acid (SÀ) on heat- and salt resistance of winter wheat (Triticum aestivum) plantlets has been studied. Treatment of bleached-out plantlets raised their surviving the after damage-heating and the influence of salt (NaCl) stress. The treatment by SA caused reversible decrease of catalase activity as activity of peroxidase and accumulation of peroxide compounds both in roots and propagules. After heating and salt stress, the contents of peroxide compounds in plantlets roots and propagules treated with SA was lower, and activity of catalase was higher than those in the control. Activity of peroxidase after heat and salt stresses in plantlets roots treated by SA was higher than in the control. At the same time, in the propagules after the action of stresses there was no difference in activity of peroxidase between the control and SA-processing variant. It is supposed that the «oxidative burst» caused by SA activates in the plantlets protective mechanisms, which provide proper response to the subsequent thermal and salt stresses.